2012
DOI: 10.1111/nmo.12016
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution colonic manometry accurately predicts colonic neuromuscular pathological phenotype in pediatric slow transit constipation

Abstract: PBAUC(1) is increased in multiple colonic segments in neuropathic pediatric STC and constitutes a sensitive and specific biomarker of neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 26 publications
2
90
2
1
Order By: Relevance
“…Colonic manometry is used to differentiate between myopathic and neuropathic motility disorders and to identify dysmotile colonic segments amenable for surgery [27,34,35]. Dysmotility of the colon is usually defined by the absence of high amplitude propagating contractions (HAPCs) and in severe cases this abnormality can be used to justify a total or partial colonic resection and/or diversion of the dysmotile colonic segment by means of an ostomy [11,[36][37][38].…”
Section: Colonic Manometry and Surgerymentioning
confidence: 99%
“…Colonic manometry is used to differentiate between myopathic and neuropathic motility disorders and to identify dysmotile colonic segments amenable for surgery [27,34,35]. Dysmotility of the colon is usually defined by the absence of high amplitude propagating contractions (HAPCs) and in severe cases this abnormality can be used to justify a total or partial colonic resection and/or diversion of the dysmotile colonic segment by means of an ostomy [11,[36][37][38].…”
Section: Colonic Manometry and Surgerymentioning
confidence: 99%
“…[2] A study of children with severe STC showed that abnormal colonic manometry was associated with histopathological findings involving neurons, ICCs, and smooth muscle. [33] Colonic dysmotility may be due to neurotransmitter imbalance, such as an excess of nitric oxide in the myenteric plexus, which could inhibit contractile activity. [34] However, the role of neurotransmitters remains unclear as multiple studies on a variety of mediators have yielded contradictory results.…”
Section: Neurogenic Constipationmentioning
confidence: 99%
“…Neuropathological loss within the enteric nervous system (ENS) has been implicated in a wide range of severe gut motility disorders, such as achalasia123, gastroparesis45, slow transit constipation678 and Hirschsprung’s disease (aganglionic megacolon)910, as well as being associated with a number of central nervous system disorders111213. Potential replacement of lost neurons using stem cell replacement is an attractive therapy for such life-limiting disorders.…”
mentioning
confidence: 99%